2018
DOI: 10.1002/prep.201700225
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Fumes at Indoor Military Shooting Ranges: Lead, Copper, Nickel, and Zinc in Different Fractions of Airborne Particulate Matter

Abstract: Small firearm shooting emits residues of energetic materials as well as heavy metals of different particle sizes into the air, posing a risk to human health. The current study assessed concentrations of Pb, Cu, Ni and Zn in 14 different size fractions of particulate matter at indoor military shooting ranges. Air samples were collected using ELPI + over two hour period and filters analysed with ICP-MS and ICP-OES.Among the studied metals, Pb concentrations were highest; however, OSHA limit values were only exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The measured PM 10 concentrations in this study were comparable with the ones reported by Orru et al [71]. The average PM concentration in one of the shooting ranges in which pistols were used is 28.9 µg/m 3 .…”
Section: Resultssupporting
confidence: 90%
“…The measured PM 10 concentrations in this study were comparable with the ones reported by Orru et al [71]. The average PM concentration in one of the shooting ranges in which pistols were used is 28.9 µg/m 3 .…”
Section: Resultssupporting
confidence: 90%
“…Notably, the available research is limited to a few studies analyzing GSR particles in an outdoor setting [29] and detecting fine particulates that would be respirable to the shooter and bystanders [28,29,35]. The determination of size deposition of GSR is important to understand due to the health effects related to different fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size distribution of organic and inorganic components from GSR is a key factor in the determination of health and environmental effects related to PM 2.5 . A limited number of studies observed the deposition and particle size in an indoor or controlled setting [10,11,28,29,35,37] but there is a lack of research, particularly in outdoor settings, for characterizing PM 2.5 from GSR. PM 2.5 is composed of a number of health-relevant components: including the aforementioned inorganic and organic species in GSR as well as black carbon which has known health effects [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…For example, by 2020, handguns and rifles accounted for 75% of annual production of total firearms in the United States 2 . Given the increasing number of firearms, tens of millions of people are exposed to smoke emissions from gun firing activities at various places every year such as military and recreational firing/training ranges [3][4][5][6][7] . Shooters can inhale the smoke directly from firearms but are also exposed from resuspended gunshot residue on their clothing, hands, and other surfaces 3,8 , however it is unclear whether such exposure can cause adverse health effects.…”
mentioning
confidence: 99%